pH Adaptation Drives Diverse Phenotypes in a Beneficial Bacterium-Host Mutualism - Nourabadi, Neda; Nishiguchi, Michele K. (Frontiers in Ecology and Evolution, 2021)
Abiotic variation can influence the evolution of specific phenotypes that contribute to the diversity of strains observed in the natural environment. Environmentally transmitted symbiotic bacteria are particularly vulnerable to abiotic fluctuations, given that they must accommodate the transition between the free-living state and the host’s internal environment. This type of life history strategy can strongly influence the success of a symbiont, and whether adapting to changes outside the host will allow a greater capacity to survive in symbiosis with the host partner. One example of how environmental breadth is advantageous to the symbiosis is the beneficial association between Vibrio fischeri and sepiolid squids (Cephalopoda: Sepiolidae). Since Vibrio bacteria are environmentally transmitted, they are subject to a wide variety of abiotic variables prior to infecting juvenile squids and must be poised to survive in the host light organ. In order to better understand how a changing abiotic factor (e.g., pH) influences the diversification of symbionts and their eventual symbiotic competence, we used an experimental evolution approach to ascertain how pH adaptation affects symbiont fitness. Results show that low pH adapted Vibrio strains have more efficient colonization rates compared to their ancestral strains. In addition, growth rates had significant differences compared to ancestral strains (pH 6.5-6.8, and 7.2). Bioluminescence production (a marker for symbiont competence) of pH evolved strains also improved at pH 6.5-7.2. Results imply that the evolution and diversification of Vibrio strains adapted to low pH outside the squid improves fitness inside the squid by allowing a higher success rate for host colonization and symbiotic competence.